ADUs : the perfect housing solution - Koones, Sheri, 1949- (Gibbs Smith, 2024)
"Accessory dwelling units (ADUs) are good for people and communities. An inside look at 25 charming, ultra-functional, extra living spaces will inspire you to build one of your own! An Accessory Dwelling Unit (ADU) is a smaller housing unit built on the same lot as a primary dwelling (also known as Additional or Auxiliary Dwelling Units) -- think granny flat, in-law unit, laneway house). It has an arrangement for sleeping, cooking, and lavatory. An ADU can be detached, attached, a garage conversion, or a basement conversion. The uses are myriad--for family members, guest spaces, rental income, or more"--